Regulatory region single nucleotide polymorphisms of the apolipoprotein E gene and the rate of cognitive decline in Alzheimer's disease. - Belbin, O; Dunn, J; Ling, Y; Morgan, L; Chappell, S; Beaumont, H; Warden, D; Smith, D; Kalsheker, N; Morgan, K (2007)
The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) in the regulatory regions of the apolipoprotein E (APOE) gene modify the well-established epsilon4-associated risk for Alzheimer's disease (AD). Sequencing of the APOE gene regulatory regions revealed four previously reported promoter SNPs and one novel SNP in the previously described macrophage enhancer (ME.1). In addition, we also studied the two classic allelic missense SNPs that define epsilon2/epsilon3/epsilon4 status in a case-control association study. Analysis of pair-wise linkage disequilibrium (LD) of the five regulatory region SNPs with classic APOE SNPs revealed a previously unreported 7 kb LD block covering the entire APOE gene, part of the promoter and 3' enhancer region. We report here that in a case-control association study (N=719) of the seven SNPs, the genotype at codon 112 captures all the information required to assess disease risk. To explore correlations with quantitative traits, 169 patients were studied in whom rates of cognitive decline were available. In addition to the epsilon4 allele, two regulatory region SNPs were associated with the rate of cognitive decline in AD patients. This study highlights the effect of APOE gene variation on risk of AD and rate of cognitive decline and demonstrates that a single SNP, which confers epsilon4 status, captures all of the risk of developing AD but two SNPs in the regulatory region may affect the rate of cognitive decline in AD patients.